As doenças psicossociais: uma análise a partir da influência do ambiente laboral frente aos novos desafios da precarização estrutural do trabalho - Silva, Fernanda Duarte da (2019)
The research seeks to understand the psychosocial diseases that affect the working class in the sphere of capitalism in Brazil, once, increasingly, workers have to maintain a posture of integral donation to labor, causing the “capture of their subjectivity”, facing to the excessively consumerist and lucrative market. Indeed, since the beginning, the labor force exploitation has been latent, since the purpose of capitalism has always been to generate profit for a minority, who controls the means of production. Thus, from Karl Marx's teachings on the exploitation of workers and the way the working class is perceived, in face of the structural crisis of capitalism, we evaluate contemporary alienation, since salaried work is responsible for the “fetishizations” of this class, which transforms the worker in an alienated, strange and objectified person. The concept of “fetishism” is inseparable from the answer to the question: “in what circumstances do workers accept the process that exploits them and makes their activity as stuff?” The explanation for this question is based on the process of alienation that takes place in the world of work, thus, it constitutes the essence of the critique to capitalism as an economic and social system. The literature review employed doctrine, legislation and statistics, through deductive method and monographic procedure, by using techniques of records and summaries. The first chapter approaches the precariousness of workers and their subjectivity, based on the class struggles that occurred in the post-industrial revolution period, which began the substitution of salaried work and the introduction of machinery, which results in accidents and illnesses. The second chapter refers to the new forms of exploitation from working class and how the work activity has ceased to generate happiness and then causes suffering. Dejours will deal with work psychodynamics to approaches the relationship between work and health in order to analyze workers from the relationship with their work reality and their ways of acting. The third chapter reflects all the transformations of production modes and the relationship of the subject with his work and how the flexibility, the lack of autonomy and specialization of certain sectors led to the alienation of worker, making the work environments sickening, since companies have reduced their work life to a “competitive stage”, once the excessive profit reduces the worker to a mere instrument of labor, causing the isolation and desolation of the subjects and the social unsustainability of long-term work. Thus, in Brazil, the “Labor Reform”, made labor relations very flexible, and also will contribute to the increase of mental illness. Therefore, more than ever, Law, as a supervisory instrument, must overlap not only to compensate injured workers, but also to act in the prevention of violations, through public policies and awareness by population in relation to seriousness of the psychosocial diseases linked to the work environment, so that they can be prevented, but also to responsible those who contribute to increase these pathologies.